Development of the Caco-2 Model for Assessment of Iron Absorption and Utilisation at Supplemental Levels - Bianca I. Mergler; Ewgenia Roth; Sylvaine F.A. Bruggraber; Jonathan J. Powell; Dora I.A. Pereira (Journal of Pharmacy and Nutrition Sciences, 2012)
Caco-2 cells may be typically used as a first step to investigate the bioavailability of different dietary and fortificant forms of iron (Fe) at low levels (< 10 µM) in tissue culture medium (TCM). Whether this model is suitable with supplemental levels of Fe (ca. 200 µM in TCM) is not clear and neither, therefore, is the choice of reference iron compound under those conditions as a ‘positive control’. Here we show that with 200 ?M iron in TCM (serum-free MEM), Fe(II) sulphate precipitates and while high levels of ascorbic acid can prevent this, it is to the detriment of the Caco-2 cell monolayer and/or it adversely affects the pH of the TCM. Adjusting the pH of TCM to account for this issue again leads to Fe precipitation, which is detectable as both a true precipitate ( 50%) and a nano-precipitate in suspension ( 20%). In contrast, Fe(III) maltol which, clinically, appears less toxic to the intestinal mucosa than Fe(II) sulphate, retains solubility at supplemental levels in cell culture medium, without adversely affecting pH or the Caco-2 cell monolayer. Moreover, the iron is also well utilized by the cells as assessed through ferritin formation. Thus Caco-2 cells may also provide a model for screening iron uptake and utilisation at supplemental levels through the cellular generation of ferritin although care must be taken in ensuring (i) appropriate TCM conditions (e.g. pH and chemical speciation of the iron) (ii) monolayer integrity (i.e. the assay response is not an artefact of toxicity) and (iii) that an appropriate reference material is used (e.g. Fe:maltol at 1:5 ratio).